Engaging hospitalized patients with personalized health information: a randomized trial of an inpatient portal. (7th December 2018) - Masterson Creber, Ruth M; Grossman, Lisa V; Ryan, Beatriz; Qian, Min; Polubriaginof, Fernanda C G; Restaino, Susan; Bakken, Suzanne; Hripcsak, George; Vawdrey, David K
Abstract: Objective: To determine the effects of an inpatient portal intervention on patient activation, patient satisfaction, patient engagement with health information, and 30-day hospital readmissions. Methods and Materials: From March 2014 to May 2017, we enrolled 426 English- or Spanish-speaking patients from 2 cardiac medical-surgical units at an urban academic medical center. Patients were randomized to 1 of 3 groups: 1) usual care, 2) tablet with general Internet access (tablet-only), and 3) tablet with an inpatient portal. The primary study outcome was patient activation (Patient Activation Measure-13). Secondary outcomes included all-cause readmission within 30 days, patient satisfaction, and patient engagement with health information. Results: There was no evidence of a difference in patient activation among patients assigned to the inpatient portal intervention compared to usual care or the tablet-only group. Patients in the inpatient portal group had lower 30-day hospital readmissions (5.5% vs. 12.9% tablet-only and 13.5% usual care; P  = 0.044). There was evidence of a difference in patient engagement with health information between the inpatient portal and tablet-only group, including looking up health information online (89.6% vs. 51.8%; P  < 0.001). Healthcare providers reported that patients found the portal useful and that the portal did not negatively impact healthcare delivery. Conclusions: Access to an inpatient portal did not significantly improve patient activation, but it was associated with looking up health information online and with a lower 30-day hospital readmission rate. These results illustrate benefit of providing hospitalized patients with real-time access to their electronic health record data while in the hospital. Trial Registration: ClinicalTrials.gov Identifier: NCT01970852.